Examining Race in Jamaica: How Racial Category and Skin Color Structure Social Inequality - Kelly, Monique D. A. (Race and social problems, 2020)
Jamaica’s social inequality is primarily held to be class-based due, in part, to the country’s perceived ethno-racial homogeneity and to the particularities of its colonial past. However, whether “race” also systemically shapes inequality in Jamaica remains understudied. To address this empirical lacuna, I examine the effects of two measures of race—categorical race and skin color—on years of schooling and household amenities using data from the 2014 AmericasBarometer social survey. I find that access to household amenities and years of schooling are starkly structured by racial category, and even more robustly by skin color, across all dimensions. The findings challenge long-held assumptions that marginalize race with regards to social inequality in Jamaica. They also suggest the importance of a multidimensional approach to studying the effects of race for understanding stratification dynamics in Jamaica. As an English-speaking, majority Afro-descent society in the Caribbean, the study’s findings add a unique country case for comparison to Latin America and may also speak to other similar contexts in the region.